PENILAIAN OBYEK WISATA DAN KARAKTERISTIK PENGUNJUNG PANTAI AIR MATA PERMAI DESA SUNGAI AWAN KECAMATAN MUARA PAWAN KABUPATEN KETAPANG - Batara, Yulinda; Rifanjani, Slamet (JURNAL HUTAN LESTARI, 2019)
One of the natural attractions in Ketapang Regency is Air Mata Permai Beach. This Tourism Object has natural attractions such as coastal scenery, sunset beauty, and others. The purpose of this study is to provide an assessment of the tourism objects and characteristics of visitors to Air Mata Permai Beach in Sungai Awan Village, Ketapang Regency. Research from May to June 2018, the research method uses a survey method by giving questionnaires or questionnaires as instruments to respondents by accidental sampling. The results of the study show that the assessment of potential objects includes the assessment of attractiveness, accessibility, accommodation obtains value (A) for the assessment of criteria for the conditions of the socio-economic environment and the assessment of supporting facilities and infrastructure gets a value (B). While the value for potential development of tourism object in Air Mata Permai Beach in Sungai Awan Village, Muara Pawan District, Ketapang Regency is 2,486.8 and the average value is 497.36 or value (A), which is potential to be developed. The characteristics of visitors Â Air Mata Permai Beach, which includes female sex, dominate around 53.30%, with the age of visitors who frequently visit an average of 13-22 years and the origin of visitors who dominate comes from Sungai Awan Village with a presentation of 26.68% because the location is close to the beach location.Keywords: , Assessment of Air Mata Permai Beach Objects, haracteristics of visitors